Reliability of Point-of-care Urine Dipstick Nitrite and Leukocyte Esterase Test in Detecting Pediatric Urinary Tract Infections: Diagnostic accuracy of urine dipstick nitrite and leukocyte esterase in pediatric urinary tract infection. - Garg, Sandeep; Yenkar, Anurag; Gore , Shivanjali; Joshi, Anuradha; Mehta , Samrat (Journal of Pediatric Nephrology, 2025)
Background and Aim: Diagnosing urinary tract infection (UTI) in children is difficult due to its non-specific clinical manifestations, difficulty obtaining a clean urine sample, and risk of renal scarring complications in the future. Urine culture is the gold standard for diagnosing UTI, but it requires 48-72 hours to report, causing delays in treatment. This study aims to evaluate the effectiveness of urine dipstick nitrite and leukocyte esterase tests in detecting UTIs in children. Methods: This cross-sectional, observational study was conducted on 79 children clinically suspected of UTI. The test results, urine dipstick test (nitrite and leukocyte esterase tests), pyuria in urine microscopy, and urine culture were checked for their sensitivity, specificity, positive predictive value, and negative predictive value. Results: Among 79 children, fever was the most common clinical manifestation, and Escherichia coli was the most common uropathogen. Compared to urine culture, the sensitivity and specificity of leukocyte esterase and nitrite tests were 83.87%, 45.83%, 9.68%, and 91.67%, respectively. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the combined test were 9.68%, 93.75%, 50.00%, and 61.64%, respectively. Similar sensitivities and specificities were calculated, considering pyuria in urine microscopy as the gold standard in rural areas. Conclusion: The leukocyte esterase test is reliable for diagnosing UTIs in children, showing good sensitivity. Higher leukocyte esterase grades indicate a higher likelihood of infection. Due to its feasibility and effectiveness, this test can replace urine microscopy for pyuria in rural areas. Nitrite tests, or their combinations, have poor sensitivity but high specificity, making them suitable for proving urinary infections in children.